Legionellosis incidents associated with spa pools, England, 2002–2018. (August 2020) - Dabrera, G.; Naik, F.; Phin, N.
Abstract: Background: Spa pools (SPs) pose risks of Legionella infection for users and bystanders. Methods: We searched the National Enhanced Legionella Surveillance System for reported SP-associated legionellosis incidents in England between 2002 and 2018 involving at least two cases. Results: For seven legionellosis SP-associated incidents, six were in commercial settings such as hotels. The median number of cases per outbreak was four (range 2–115). Conclusion: SP-associated legionellosis incidents were mainly located in commercial settings with a wider range of cases than those recognised in previous publications, reinforcing the need for effective environmental controls for SPs in a range of settings. Highlights: Legionella outbreaks are recognised to occur sporadically and are commonly recognised as being explosive in nature, with potentially large numbers of cases occurring within short periods of time. More clearly understanding the potential spectrum of incidents supports the provision of environmental advice to prevent future incidents. This study demonstrates that SP-associated legionellosis incidents were mainly located in commercial settings with the potential for a large number of people to be exposed, as demonstrated by some incidents with large numbers of cases. This reinforces the need for effective environmental controls for SPs in a range of settings.